The Psychological Condition of the Parents of Children Suffering from Spinal Muscular Atrophy - Nihayati, Hanik Endang; Fauziah, Siska Nurul; Hidayati, Laily; Yunita, Fildzah Cindra (International Journal of Psychosocial Rehabilitation, 2020)
Fatigue during the treatment period results in a negative response when taking care of their disabled child. A change in the behavior of the parents has an impact on their physical and mental health. This study aims to explore the experience and psychological condition of the parents with children suffering from Spinal Muscular Atrophy. This study was qualitative research with a phenomenological study approach. The participants totaled as many as 23 families selected through purposive sampling. Collecting the data was done through in-depth interviews analyzed thematically using Colaizzi’s steps. The results show that the experience of the parents of children suffering from Spinal Muscular Atrophy consists of 17 themes formed of 5 categories and 33 sub-themes. The parents’ experience related to their children suffering from Spinal Muscular Atrophy can be described referencing the following: 1) The parent’s understanding of the childhood illness, 2) Parental burden, 3) The influence of illness on the family, 4) Self-obstacles, 5) Infrastructure barriers, 6) Grieving, 7) Sources of support, 8) Type of support, 9) Division of roles, 10) Coping mechanisms, 11) Skill improvements, 12) Efforts when looking for help, 13) The development of the children suffering from Spinal Muscular Atrophy, 14) Co-morbidities in the children suffering from Spinal Muscular Atrophy, 15) Substitute caregivers, 16) Acceptance and 17) Policy. The experience of the parents with children suffering from Spinal Muscular Atrophy in Indonesia is one that requires support from within themselves, from within their families and socially to reduce the burden and obstacles felt by the parents. It is expected that health care agencies and the parents can provide appropriate care for the children suffering from Spinal Muscular Atrophy.